Clinical comparison between direct anterior approach and posterior lateral approach in total hip arthroplasty and risk factors for lateral femoral cutaneous nerve injury - Yan, Jian-feng; Zhao, Le; Li, Qiang (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to compare the clinical outcomes of total hip arthroplasty (THA) using the lateral decubitus direct anterior approach (DAA) vs. the traditional posterior lateral approach (PLA), and to explore the risk factors and predictive models for lateral femoral cutaneous nerve (LFCN) injury following DAA-THA.MethodsTwo hundred patients undergoing primary unilateral THA were randomly assigned to the DAA group and the PLA group, with 100 cases in each group. Clinical data, surgical parameters, postoperative pain scores, and other relevant data were recorded, and the differences between the two groups in terms of treatment outcomes and postoperative recovery were analyzed.ResultsCompared to the PLA group, patients in the DAA group had shorter incisions, reduced blood loss and drainage, shorter hospital stays, decreased postoperative inflammatory markers, and lower pain scores. However, the incidence of postoperative LFCN injury was higher in the DAA (DAA:24patients, 24%, PLA:2patients, 2%) group, although most cases resolved within one year. Univariate analysis showed that diabetes, preoperative serum CK levels, serum IL-6, and TNF-α levels at postoperative day 3 were associated with early LFCN injury, while diabetes, BMI, and postoperative inflammation were significantly associated with persistent LFCN injury. Binary logistic regression analysis identified serum IL-6 and TNF-α levels at postoperative day 3 as independent risk factors for persistent LFCN injury. The established predictive model demonstrated good discrimination.ConclusionDespite slightly longer surgical duration, DAA demonstrated significant advantages in reducing early pain, blood loss, and hospital stay. However, postoperative LFCN injury warrants attention, especially in patients with diabetes and postoperative inflammatory reactions.